Phenomenological Approaches to Adolescent Girls’ Perceptions of Storywriting-based Design Thinking Focused on Aggression - Zahra Abolhassani (International Journal of School Health)
Background: The design thinking approach is a method based on problem-solving that has recently become popular in the new ways of teaching different fields. Therefore, the present study aimed to investigate the lived experiences of secondary school students in implementing the extraordinary curriculum based on design thinking with the use of story-writing tools to reduce aggression.Methods: This study applied a phenomenology method. The study included middle school girls in Baharestan city, Tehran Province, Iran. A total number of 78 students were selected using convenience sampling method. To collect data, structured interview was performed from May 13, 2023 to May 17; 2023. Data analysis was done using Colaizzi’s 7-step method. Data validation was done through strategies such as reviewing interviewee transcripts, coding, and review by educational science experts.Results: The findings of the interviews revealed three main axes: factors influencing aggression including emotions (such as hatred, jealousy, grudge, and low self-esteem) and social interactions (negative human behaviors towards others and negative behaviors in discussions and conversations); ways of controlling and managing aggression including practical techniques and sub-themes (thinking-based techniques, social interaction-based techniques, action-based techniques); and the curriculum learned from design thinking including cognitive aspects (creativity, decision-making, re-creation) and communication processes (consultation, interaction, empathy).Conclusion: The results of the present study will provide psychologists and educators with a new perspective to prevent or reduce aggressive behaviors in educational environments. Also, our results indicated that aggression is experienced in a wide range of emotions, including disgust, self-deprecation, hatred, and jealousy, as well as behaviors and the use of words in communication. Accurate recognition of these experiential factors and elements can have significant implications for diagnosis and treatment. Therefore, the findings can somewhat emphasized the classification of these effective factors in creating aggression and the management and control strategies of aggression.